The Effects of Gender Discrimination in DSGE Models - Daniel Stempel; Ulrike Neyer (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
This paper theoretically analyzes the macroeconomic effects of gender discrimination against women in the labor market in a New Keynesian model. We extend standard frameworks by including unpaid household production in addition to paid labor market work, by assuming that the representative household consists of two agents, and by introducing discriminatory behavior on the firms' side. We find that, in steady state, this discrimination implies that women work inefficiently more in the household and less in the paid labor market than men. This inefficient working time allocation between women and men leads to a discrimination-induced gender wage gap, lower wages for women and men, lower ag-gregate output, and lower welfare. The analysis of dynamic effects reveals that households benefit less from positive technology shocks. Moreover, the transmission of expansionary monetary policy shocks on output and ination is lower in the discriminatory environment.
Keywords: D13; D31; E32; E52; J71; 330; New Keynesian Models; Gender Discrimination; Household Production; Monetary Policy Transmission